Cinobufacini Injection Improves the Efficacy of Chemotherapy on Advanced Stage Gastric Cancer: A Systemic Review and Meta-Analysis. (4th September 2018) - Zhang, Xing; Yuan, Yuan; Xi, Yupeng; Xu, Xinyao; Guo, Qiujun; Zheng, Honggang; Hua, Baojin
Abstract : Gastric cancer has a high morbidity and mortality. Chemotherapy regimens are routine advanced stage gastric cancer (AGC) treatment protocols, but most of these drugs have side-effects such as myelosuppression and gastrointestinal disorders. Cinobufacini, an extractive from TCM, could suppress cell proliferation and inhibit gastric cancer. In this study, we comprehensively reviewed the literature on the efficacy comparison between Cinobufacini injection combined with chemotherapy and chemotherapy solely used in AGC treatment. We extracted data for from six electronic databases to evaluate the efficacy of Cinobufacini injection on AGC patients. Twelve studies with a total of 853 patients were finally included in our study. The results indicated that Cinobufacini injection could increase response rate and disease control rate of chemotherapy on AGC, improve the life quality of AGC patients, increase leukocytes, improve anemia, improve hand-foot syndrome induced by chemotherapy, and relieve cancer pain. This study has its own limitations that prevented us from drawing a definite conclusion and more well-designed clinical trials of TCM are needed.